New security frontiers critical energy and the resource challenge - Krishna-Hensel, Sai Felicia (Global interdisciplinary studies series, 2016)
The author brings together a wide range of topics focusing on critical resource availability impacting upon global security and the geopolitical ramifications of resource competition. The volume addresses the development of strategic thinking on these issues and underscores the increasing awareness that this is a critical area of concern in the twenty-first century global landscape.